2011
DOI: 10.1182/blood-2010-12-324632
|View full text |Cite
|
Sign up to set email alerts
|

Self MHC class I–licensed NK cells enhance adaptive CD8 T-cell viral immunity

Abstract: MHC class I (MHC I) IntroductionNatural killer (NK) cells are essential mediators of virus immunity 1 ; their deficiency in humans or depletion from mice leads to uncontrolled viral replication and poor clinical outcome. 2-4 MHC class I (MHC I) molecules, which are ligands for polymorphic human KIR and mouse Ly49 receptors, play a critical role in NK-cell activation and selftolerance. The absence of self-MHC I renders cells susceptible to NK-cell cytotoxicity. [5][6][7] Moreover, the interaction between MHC I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 54 publications
5
56
1
Order By: Relevance
“…The timing of NK cell virus control may be critical for protection from organ damage. NK cells are innate immune responders, while MCMV-specific T cells require 4 to 5 days to develop (31,41,47). The antiviral effect of adaptive immunity in the spleen was not sufficient to protect the gland, since Rag1 mice did not succumb to secretory dysfunction after low-dose infection.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of NK cell virus control may be critical for protection from organ damage. NK cells are innate immune responders, while MCMV-specific T cells require 4 to 5 days to develop (31,41,47). The antiviral effect of adaptive immunity in the spleen was not sufficient to protect the gland, since Rag1 mice did not succumb to secretory dysfunction after low-dose infection.…”
Section: Discussionmentioning
confidence: 99%
“…These differences might be related to different mouse strains or the different source of virus used. In recent work, Stadnisky et al (47) showed that NK cell activation by the missing-self mechanism also resulted in faster recovery of splenic cDCs after their initial drop and in an improved CD8 ϩ T-cell response. Thus, the more robust CD8 ϩ T-cell response in mice infected with ⌬m157 virus looks like a paradox since it is accompanied by a depletion of splenic cDCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, Andrews et al (3) have shown that an NK cell response mediated through Ly49H-m157 interaction limits the long-term efficacy of specific CD8 ϩ and CD4 ϩ T cells and that this is a consequence of an altered frequency and duration of infection of antigenpresenting cells. More recently, Stadnisky and colleagues (47) have demonstrated a role for inhibitory NK receptors in the CD8 ϩ T-cell response to MCMV. Although these authors did not exclude a role for MCMV-specific activating NK receptors in their model, they provided first evidence to propose that the recognition of infected cells by licensed Ly49G2 ϩ NK cells results in a faster recovery of splenic cDCs and an enhanced antigen-specific CD8 ϩ T-cell response.…”
mentioning
confidence: 99%
“…51 This DC lysis also reduces the various cytokines produced by DCs, which can hamper the overall immune response as well. NK cells can also promote DCs through IFNγ production, 52 CD40-CD40L interaction, 53 or GM-CSF production. Thus, a number of pathways and mechanisms exist for NK–DC interactions and reciprocal regulation of both populations during immune challenge.…”
Section: Nk Regulation During Cancermentioning
confidence: 99%